Towards a science of touch, part II - Hsu, E (Carfax Publishing, 2000)
This paper concerns a pre-modern 'science of touch' - Chinese pulse diagnostics - and it discusses four different means by which Chinese physicians represented and described the tactile experience of sensing different pulses: (a) by use of similes, (b) with descriptive verbs and adjectives, (c) by comparing one pulse to the other and contrasting the two from each other, and (d) by a visual representation of the tactile experience. The material for the article is taken from treatises in early modern Europe, which contain translations of works on Chinese pulse diagnostics, but the questions with which I approach this textual material relate to an 'anthropology of sensory experience'. It is argued that - unlike other modalities of perception - tactile perception arises from a mutual involvement of touching subject and touched object. While such melding between subject and object makes touch an excellent non-verbal means of communication, one would expect that it is difficult to assess in an objective way. Yet the article shows ingenious ways with which Chinese physicians tackled the problem.